Development of building assessment criteria framework for implementing the issuance certificate occupancy in Jakarta with Genetica Algoritm method - M. Fajar Prasetyo; Ayomi Dita Rarasati; Henki Wibowo Ashadi (Publikasi Indonesia, 2025)
A building is considered ready for use once it obtains a Certificate of Occupancy, which serves as a regulatory mechanism for overseeing building activities. To measure the quality level achieved in a completed building project, numerous assessment tools and methods have been developed globally to measure building performance. This study aims to create an evaluation system based on a scoring methodology. To develop the framework, seven prominent building assessment methods were analyzed, focusing on their application processes, primary criteria, and sub-criteria. Surveys were conducted involving construction experts and respondents familiar with quality and feasibility building assessment to incorporate their insights into the local construction context of Jakarta. The genetic algorithm method was used to analyze the survey data, leading to the identification of 12 criteria and 39 sub-criteria as the most suitable for assessing the implementation of the Certificate of Occupancy in Jakarta. These criteria include structural integrity (5%), fire safety (20%), mechanical, electrical, and plumbing (MEP) systems (8%), accessibility (8%), drainage systems and waste management (5%), functionality testing (8%), environmental quality (6%), sociocultural and functional aspects (8%), technical quality (8%), construction area quality (8%), energy consumption (8%), and health-related building requirements (8%).